Development of an advanced nano-satellite (VELOX-I) - power quality and monitoring system - Yong, Haur Ming. (2013)
This report focused on 5 areas in the development of an advanced nano-satellite (VELOX-I) namely cell balancing system, power system redundancy, temperature monitoring system, batteries state-of-charge monitoring system and development of battery management system with enhanced kill switch for pico-satellite. The first part of the report covered the introduction of nano-satellite to understand the systems and functions of nano-satellite (VELOX-I). It was followed by literature review on the 5 areas of development.